Atomic Scale Insight into Corrosion Inhibition: DFT Study of 2-Mercaptobenzimidazole on Locally De-Passivated Copper Surfaces. Issue 12 (16th December 2021) - Chiter, Fatah; Costa, Dominique; Maurice, Vincent; Marcus, Philippe
Abstract : A key factor for effective inhibition by organic molecules of the initiation of localized corrosion by pitting is their ability to form a protective organic film in locally de-passivated zones exposing the bare metal next to the oxide-covered surface. Herein, based on quantum chemical DFT calculations, we study the chemistry of the interface between 2-mercaptobenzimidazole (MBI) and a copper surface partially covered by a Cu2 O passive oxide film. The results show the adaptability of the molecule to adsorb strongly on the different zones, oxide or metal, of a locally de-passivated surface. However, differences in the local adsorption configurations, involving covalent bonding with H-bonding depending on oxide or metal and on conformer, thione or thiolate, lead to the formation of an inhomogeneous organic film. Increasing order of local adsorption strength is oxide walls < metal surface < oxide surface < oxide edges for the thione species, whereas there is no significant difference of local adsorption strength for the thiolate species. Our results suggest that both species of MBI can heal the oxygen and copper low coordinated sites as well as can protect the exposed metal surface, thus enhancing the barrier properties of the passivated surface even when locally defective.